3D Printed Metamaterial Capacitive Sensing Array for Universal Jamming Gripper and Human Joint Wearables. Issue 5 (9th February 2021) - Loh, Leon Yeong Wei; Gupta, Ujjaval; Wang, Yingxi; Foo, Choon Chiang; Zhu, Jian; Lu, Wen Feng
Abstract : Existing stretchable capacitive sensor arrays face challenges in decoupling normal forces and stretch stimuli which restrict its applications into soft robotics. Herein, a metamaterial capacitive sensor array with 6 × 6 sensors is developed for the detection of normal forces on curved deforming surfaces common to both the soft universal jamming gripper and human elbow. The fabrication process involves the 3D printing of carbon black thermoplastic polyurethane (PI–ETPU) electrodes and thermoplastic polyurethane (TPU) insulation based on commercially available multimaterial fused deposition modeling (FDM). This metamaterial capacitive sensor array is unaffected by a uniaxial stretch of up to 21.6% and remains capable of detecting normal forces. The sensor array structure possesses a negative Poisson's ratio which is desirable for improving compliance and conformability to adhered expanding surfaces. Consequently, normal force‐distribution and proximity detection capabilities on curved deforming surfaces are demonstrated on a soft universal jamming gripper for measuring gripping forces and identifying object shapes. Conformal force‐sensing joint wearable on a human elbow with an individualized Poisson's ratio is explored as another application. The possibility of programming Poisson's ratio of a metamaterial capacitive sensing array opens new avenues for potential sensing applications into soft robotics and personalized wearables. Abstract : Soft stretchable sensors are becoming essential in enabling force and proximity sensing capabilities on curved deforming surfaces in unstructured environments. Mechanical metamaterials designs fabricated by affordable 3D printing are investigated as a platform to improve compliance and conformality of existing soft sensor arrays, for diverse applications in universal jamming gripper and elbow force‐sensing wearables.